Model PANTAU Berbantuan Media Interactive Map: Upaya Meningkatkan Keterampilan Berpikir Kritis dan Kolaborasi Murid - Lina Indriyanti; Diani Ayu Pratiwi (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to improve critical thinking and collaboration skills of fourth-grade students in the IPAS subject through the implementation of the PANTAU learning model assisted by Interactive Map media. The PANTAU model integrates Problem Based Learning (PBL), Contextual Teaching and Learning (CTL), and Team Games Tournament (TGT), designed to create active, contextual, and collaborative learning. The Interactive Map serves as a digital interactive tool that facilitates material exploration, group discussions, and educational game-based quizzes. This research employed a qualitative approach with Classroom Action Research (CAR), conducted in four cycles involving 27 fourth-grade students at SDN Sungai Miai 10 Banjarmasin. The findings revealed a significant improvement in students’ critical thinking skills, from only 4% categorized as “highly skilled” in the first meeting to 85% in the fourth meeting. Similarly, collaboration skills increased from 33% to 93% of students categorized as “highly skilled.” These results demonstrate that the integration of the PANTAU model with Interactive Map media effectively fosters more active, interactive, and meaningful learning, while successfully achieving the predetermined indicators of success.